MANAJEMEN LABA BERDASARKAN ASET PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN - Halimah, Imar; Wahyuningsih, Titi (Jurnal Ilmiah Publika, 2023)
This study aims to determine the effect of deferred tax assets and deferred tax expenses on earnings management in primary consumer goods sector companies listed on the IDX for the 2017-2021 period. Taxation has criteria provisions regarding the measurement and recognition of components contained in the financial statements, but these measurements are not always the same as commercial accounting principles. Deferred tax assets and deferred tax expenses can detect companies doing earnings management, because there are differences in recording between commercial and fiscal financial statements that cause temporary differences.This type of research is explanatory research. Explanatory research with explanatory survey research methods. The sample withdrawal method in this study used purposive sampling, so that the sample obtained was 8 companies. Data analysis methods with descriptive statistics, multiple linear regression and hypothesis testing using eviews 10 software. The results showed that partially deferred tax assets affect earnings management while deferred tax expenses have no effect on earnings management. Simultaneously, it shows that deferred tax assets affect earnings management in primary consumer goods sector companies listed on the IDX for the period 2017-2021.